2019
DOI: 10.2147/cia.s213006
|View full text |Cite
|
Sign up to set email alerts
|

<p>The effects of a dyadic strength-based empowerment program on the health outcomes of people with mild cognitive impairment and their family caregivers: a randomized controlled trial</p>

Abstract: PurposeAs an intermediate prodromal stage of dementia, mild cognitive impairment (MCI) causes functional, emotional, and social challenges for both of the person with MCI (PwMCI) and their family caregiver. However, major attention has only been placed on the PwMCI’s for cognitive training. This study evaluated a more comprehensive intervention, which integrated both strength-based and empowerment approaches, to address their complex needs in a dyadic fashion.Patients and methodsThis randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 29 publications
0
45
0
4
Order By: Relevance
“…Spouse/partners tended to comprise most of the samples (62%) across the 15 studies reporting this information, with adult children/ in-law the other main group of caregivers (on average, 29% of samples across 14 studies). When reported, co-residence of the caregivers with care recipients tended to correspond closely with spousal caregiving, although a significant exception was Yu et al's (2019) work from Hong Kong where co-residence was 100% despite 61% of their sample being child/in-law caregivers. Although it was of interest how long caregivers had been providing assistance to the care recipient, how much time they spent providing care, and how many co-morbidities the care recipients had, this information was sparsely and inconsistently reported so could not be meaningfully summarized.…”
Section: Description Of Included Studiesmentioning
confidence: 96%
“…Spouse/partners tended to comprise most of the samples (62%) across the 15 studies reporting this information, with adult children/ in-law the other main group of caregivers (on average, 29% of samples across 14 studies). When reported, co-residence of the caregivers with care recipients tended to correspond closely with spousal caregiving, although a significant exception was Yu et al's (2019) work from Hong Kong where co-residence was 100% despite 61% of their sample being child/in-law caregivers. Although it was of interest how long caregivers had been providing assistance to the care recipient, how much time they spent providing care, and how many co-morbidities the care recipients had, this information was sparsely and inconsistently reported so could not be meaningfully summarized.…”
Section: Description Of Included Studiesmentioning
confidence: 96%
“…Our study findings showed that the older people defined respect in family relationships as attention to their preferences and participation in familial occasions. It is believed that appropriate planning for life activities based on older people’s abilities and preferences is associated with improved feelings of efficiency, self-esteem, pleasure, comfort, creativity and autonomy [ 43 , 44 ]. Older people in various cultures commonly wish that children would pay greater attention to their parents and give them gifts on special occasions.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 A psychological intervention called dyadic strength-based empowerment program (D-StEP-MCI) improved the cognitive and NPS of individuals with MCI and reduced overall depression of the care dyads. 43 A type of training designed to help individuals with MCI adapt to memory loss, called memory support system (MSS) training, may help promote patients' level of functioning and an improved sense of memory self-efficacy, leading to improved mood and less caregiver burden over time. 44…”
Section: Dyadic Interventionsmentioning
confidence: 99%